2015
DOI: 10.1007/s11096-015-0161-9
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of cutaneous adverse drug reactions in a teaching hospital

Abstract: Cutaneous adverse reaction patterns and their causes vary as the result of changing use of drugs. In India, antibiotics are responsible for the majority of the cutaneous adverse drug reactions, and maculopapular rash is the side effect that is most reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 10 publications
(15 reference statements)
1
19
0
Order By: Relevance
“…A cross-sectional observational study in oral and maxillo-facial surgery and general medicine department with outdoor patients found that antibiotics and NSAIDs contributed to 40 (53%) and 30 (40%) of the total 75 skin reactions, respectively. Maculopapular rash, urticaria, fixed drug eruption and angioedema were the most common reactions observed in this study with anticonvulsants induced Steven-Johnson syndrome (SJS) predominantly in general medicine department patients (Chattopadhyay and Chakrabarti, 2012 (Chopra et al, 2015). Most of the cutaneous ADRs were exanthematous eruptions type [37 (33.3%)] and were reported with antimicrobial agents [77 (69.4%)] out of 111 cases of cutaneous ADRs reportedin another retrospective study.…”
Section: Cutaneous Adverse Drug Reactionsmentioning
confidence: 72%
“…A cross-sectional observational study in oral and maxillo-facial surgery and general medicine department with outdoor patients found that antibiotics and NSAIDs contributed to 40 (53%) and 30 (40%) of the total 75 skin reactions, respectively. Maculopapular rash, urticaria, fixed drug eruption and angioedema were the most common reactions observed in this study with anticonvulsants induced Steven-Johnson syndrome (SJS) predominantly in general medicine department patients (Chattopadhyay and Chakrabarti, 2012 (Chopra et al, 2015). Most of the cutaneous ADRs were exanthematous eruptions type [37 (33.3%)] and were reported with antimicrobial agents [77 (69.4%)] out of 111 cases of cutaneous ADRs reportedin another retrospective study.…”
Section: Cutaneous Adverse Drug Reactionsmentioning
confidence: 72%
“…[ 9 10 ] There was a male preponderance in our study which has been noted previously by other workers as well. [ 9 10 11 12 ] However, a few other studies[ 13 14 15 ] have reported females to be affected more commonly.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 12 17 18 19 ] Patel and Marfatia[ 12 ] studied 200 patients and reported FDE in majority (61; 30.5%), followed by urticaria (37; 18.5%) and MPR (36; 18%), a finding almost similar to ours. However, a few studies[ 10 11 14 ] have reported MPR to be the most common pattern. Hiware et al .,[ 10 ] in a study on 872 patients over 4 years, observed MPR as the commonest CADR (329; 37.7%), followed by FDE (150; 17.2%) and urticaria (127; 14.5%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations